Leap motion ®: Signal preservation and medical training system - Pongphan Pongpanitanont (2018)
© 2014 IEEE. The objective of this work is develop the paradigm for training subject with dyslexia. Leap motion sensor used to develop the training program for subject's evaluation. This paper studies about fingers position data interpolation from Leap motion sensor. The fingers data used to control the visual hands to play a piano. Linear interpolation of Leap motion data show the signal smoothing than original signal. In term of high sampling rate (100Hz) the signal outcome has worse prognosis than lower sampling rate (1-10Hz).